Principles and practice of surgery - Garden, O. James (Elsevier, 2012)
A surgical companion textbook to the international medical bestseller "Davidson's Principles and Practice of Medicine". It is suitable for both the surgical student and trainee, guiding the reader through key core surgical topics which are encountered throughout an integrated medical curriculum as well as in subsequent clinical practice